Transformative PdPc Approach in Civil Engineering Integrated Design Project for Enhancing Student Learning Experiences and Nurturing Future-Ready Graduates - Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don (UMK Press, Universiti Malaysia Kelantan, 2021)
To enhance student learning experiences in practicing civil engineering skills, Integrated Design Project (IDP) courses using a transformative learning & coaching (PdPc) approach were designed. A role-play method acting as a consultant firm was adopted to expose the students with the real working environment before joining the industry upon their graduation. Mentoring and coaching methods provided by both academic experts and professional engineers through knowledge-sharing sessions were conducted. The main target of the IDP courses was not only to produce graduates with good technical knowledge, but also to be future-ready engineering practitioners.